143k views
3 votes
Use the zero product property to find the solutions to the equation 2x2 + x - 1 = 2

a) x= -1/2 or x =2
b) x= -2 or x =1/2
c) x= -3/2 or x =1
d) x= 1 or x= 3/2​

User Guiomie
by
4.7k points

1 Answer

3 votes

Answer:

C

Explanation:

Given

2x² + x - 1 = 2 ( subtract 2 from both sides )

2x² + x - 3 = 0

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 2 × - 3 = - 6 and sum = + 1

The factors are - 2 and + 3

Use these factors to split the x- term

2x² - 2x + 3x - 3 = 0 ( factor the first/second and third/fourth terms )

2x(x - 1) + 3(x - 1) = 0 ← factor out (x - 1) from each term

(x - 1)(2x + 3) = 0

Equate each factor to zero and solve for x

x - 1 = 0 ⇒ x = 1

2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
(3)/(2)

User Nilesh Rathore
by
5.1k points